Study of Geophilic Keratinophilic Fungi in Public Squares of Jaboticabal-SP (Revista Brasileira Multidisciplinar, 2009)
Considering the use of public parks as a source of leisure for the population, who maintain an intense and direct contact with the ground, which is a potential source of contamination by different causative agents of mycosis, the purpose of the research was to identify genera of keratinophilic geophilic fungi in the soil of squares in Jaboticabal-SP. 60 soil samples from 15 public squares, and 4 samples of each square were selected and collected. To isolate the soil fungi, we used the method of Vanbreuseghem (1952), modified by Machado (1977). Later the fungi were cultivated in Petri dishes containing Sabouraud Agar added to chloramphenicol, and were incubated at room temperature for about ten days. The grown colonies were isolated in test tubes to obtain pure culture. Macroscopic and microscopic analyses of isolated colonies were made and they were identified at a gender level with the aid of an identification guide. From 60 soil samples collected, 39 were positive for keratinophilic fungi, of which 90 fungic colonies were isolated, being identified the genera Penicillium spp. Fonsecaea spp., Rhizopus spp., Microsporum spp., Fusarium spp., Phialophora spp., Aspergillus spp., Acremonium spp., Nigrospora spp., Trichoderma spp., Bipolaris spp., Aureobasidium spp., Curvularia spp., Mucor spp. and Mycelia sterilia. The results allowed us to conclude that these soils represent a diverse microflora capable of degrading keratin substrates, allowing an assessment of the epidemiological potential represented by the soil in the squares of the city of Jaboticabal-SP.
Keywords: Filamentous fungi; Keratinophilic fungi; Geophilic fungi; Public squares; Mycoses.